Fundamento y Condición del Derecho Internacional - OROZCO, LUIS ERNESTO (Tirant lo Blanch, 2020)
https://editorial.tirant.com/mex/libro/fundamento-y-condicion-del-derecho-internacional-luis-ernesto-orozco-torres-9788413550329?busqueda=Luis+Ernesto+Orozco+Torres&